Association of Pediatric Obesity and Migraine With Comparison to Tension Headache and Samples From Other Countries. (March 2015) - Eidlitz-Markus, Tal; Haimi-Cohen, Yishai; Zeharia, Avraham
The link between body weight and headache has hardly been examined in children. The aim was to evaluate the association of obesity and migraine in selected pediatric patients and compare the findings with the literature. Data on clinical symptoms, headache type, and body mass index standard deviation score were derived from the medical files of 245 patients with migraine and 87 with tension headache. Comparison of the 3 subgroups of migraine patients of normal weight, overweight, and obese with the corresponding body mass index standard deviation score subgroups of patients with tension-type headache yielded no statistically significant differences in frequency of headache attacks per month, or duration of headache attacks in hours. These results call into question earlier reports linking headache and obesity in children. Differences in findings between our study and those in the literature highlight several factors that should be addressed in further studies. A larger sample size may reveal more significant results.